Children at risk for cerebral palsy early identification and effect of early intervention - Kari Anne I. Evensen (Fysioterapeuten, 2011)
Introduction: Cerebral palsy (CP) is a permanent neurological disorder occurring in two per thousand children. The risk is increased among children born prematurely. The plasticity of the brain is highest from 2-3 months before and until 6-8 months after term. Still, median age for diagnosing CP is 15 months. Aim: The aim of this article is to address how physiotherapists might be able to identify and treat children at risk for CP before they are diagnosed with CP. The article is based on searches in commonly used databases over peer-reviewed papers. Result: The literature shows that children at risk for CP can be identified already at three months of age by combining examination of the quality of movements with findings from neurological examination and brain imaging. However, studies on effect of different interventions on motor development have shown inconsistent results. Recent physiotherapy interventions have shown positive results. There are several problems in studying effect of physiotherapy, due to the fact that CP is a very heterogeneous condition. Studies in the future may benefit from focusing on subgroups of children with risk for CP.